Leicester Cough Questionnaire validation and clinically important thresholds for change in refractory or unexplained chronic cough. (May 2022) - Nguyen, Allison Martin; Schelfhout, Jonathan; Muccino, David; Bacci, Elizabeth D.; La Rosa, Carmen; Vernon, Margaret; Birring, Surinder S.
Introduction: The Leicester Cough Questionnaire (LCQ), a cough-specific quality-of-life measure, evaluates the impact of cough across physical, psychological, and social domains in patients with chronic cough (CC). This study assessed the psychometric properties of the LCQ. Methods: Data from a phase IIb, randomized controlled trial of the P2X3-receptor antagonist gefapixant were analyzed (NCT02612610). Subjective [Cough Severity Diary, cough severity visual analogue scale, and patient global impression of change (PGIC)] and objective (awake and 24-h cough frequency) data were used to validate the LCQ for use in patients with refractory or unexplained CC (RCC and UCC, respectively). Psychometric analyses included confirmatory factor analyses, internal consistency and test–retest reliability, validity, responsiveness, and estimated within-patient thresholds for clinically meaningful change. Results: Model-fit values for the proposed three-factor LCQ domains and most individual items were acceptable. Analyses suggest that a mean improvement ranging from 1.3 to 2.3 points for the LCQ total and ⩾0.8,  ⩾0.9, and ⩾0.8 points for physical, psychological, and social domain scores, respectively, had the best sensitivity and/or specificity for predicting patient ratings of improvement on the PGIC. Conclusions: The LCQ is a valid and reliable measure to evaluate cough-specific quality of life and is a fit-for-purpose measure for use in patients with RCC or UCC. Although a single threshold for defining clinically meaningful change depends on the context of use, the results can help guide both treatment decisions and drug development. Therefore, clinicians may consider a ⩾1.3-point increase in the LCQ total score as clinically meaningful.